Pelanggaran Etika Pariwara Indonesia dalam Feed Instagram Ms Glow Men - Putra, Justin Mahendra; Dias, Ega; Hakiim, Naufal (Universitas Muhammadiyah Magelang, 2023)
This research aims to analyze violations of Indonesian Advertising Ethics in the Ms Glow for Men Instagram feed. This study used a descriptive qualitative method. This analysis was used to identify violations of Indonesian Advertising Ethics that occurred in the Ms Glow for Men Instagram feed advertisement. This research found that there was a violation of Indonesian Advertising Ethics because animated characters were used as content that gave a bad image because it showed racism towards these characters. This advertisement also has the potential to violate the Copyright Act.